Kepemimpinan Kerajaan Sultanah dalam Perubahan Sosial di Aceh, 1641-1699 - Melinda Rahmawati; Desvian Bandarsyah; Sulaeman Sulaeman (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2024)
This research aims to interpret and photograph the social changes that were present during the sultanate's leadership period throughout 1641-1699. With the crowning of a woman as the leader of a country, of course, turmoil has arisen in various spheres of society. Including encouraging the emergence of systemic and comprehensive social changes in the midst of Acehnese society to date. This study uses a qualitative-explanatory method with a literature study approach that visualizes and photographs the causative factors and forms of social change in the leadership of the sultanate in the Sultanate of Aceh Darussalam. The results of this study show that there have been several social changes that have a positive impact and are rooted to date for the people of Aceh. Gender equality in various social spheres, the formation of the Three Sagi Federation (Aceh Lhee Sagoe), and the opportunity to contribute to the military world have made Acehnese women more steadfast in stepping in accordance with the guidance of their customs and religious teachings. The conclusion of this study shows that the leadership of the sultanah is not only a symbol of awareness of the equal roles of men and women in society. Although the various policies set were not a few controversial and gave rise to scholars and nobles who strongly opposed them. Furthermore, the social changes caused have proven to have advanced the next generation, protected all the people under their protection, and become a down-to-earth cultural heritage in the midst of Acehnese society.